Good morning, gorillas - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2002)
The magic tree house takes Jack and Annie to an African rainforest, where the siblings encounter gorillas and learn to communicate with them.
A stepping stone book.
Keywords: Gorilla; Human-animal communication; Time travel; Magic; Tree houses